2022
DOI: 10.3390/plants11020219
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Embryo Sacs and Fruit Set in Different Plum (Prunus domestica L.) Cultivars Grown under Norwegian Climatic Conditions

Abstract: Compatibility and synchrony between specialized tissues of the pistil, female gametophytes and male gametophytes, are necessary for successful pollination, fertilization, and fruit set in angiosperms. The aim of the present work was to study the development and viability of embryo sacs, as well as fertilization success, in relation to the fruit set of the cultivars ‘Mallard’, ‘Edda’, ‘Jubileum’, and ‘Reeves’, under specific Norwegian climatic conditions. Emasculated, unpollinated, and open-pollinated flowers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The highest percentage of viable ovules was observed with the 'Jubileum' cultivar at all temperatures. This cultivar exhibited the highest percentage of viable and fertilized embryo sacs and fruit sets, whereas the lowest was observed in 'Reeves', as Cerović et al [48] reported. Previous research by Fotirić Akšić et al [1] indicated that 'Jubileum' has a longer effective pollination period of five days, in contrast to 'Edda', 'Mallard', and 'Reeves', where it lasts only three days.…”
Section: Discussionsupporting
confidence: 49%
“…The highest percentage of viable ovules was observed with the 'Jubileum' cultivar at all temperatures. This cultivar exhibited the highest percentage of viable and fertilized embryo sacs and fruit sets, whereas the lowest was observed in 'Reeves', as Cerović et al [48] reported. Previous research by Fotirić Akšić et al [1] indicated that 'Jubileum' has a longer effective pollination period of five days, in contrast to 'Edda', 'Mallard', and 'Reeves', where it lasts only three days.…”
Section: Discussionsupporting
confidence: 49%
“…At that time, fruit cultivation was mainly conducted within monasteries, from where the practice then spread [2]. Plum production is currently located in the most suitable climatic regions, along the fjord sides in Western Norway and around lakes in Eastern Norway [3], where the short and relatively cool growing season limits the choices of plum cultivars that can be grown [4].…”
Section: Introductionmentioning
confidence: 99%